(untitled) - Rose, Richard (Cambridge, 2002)
Russians want free elections and order. Although their political elites have had no difficulty in supplying candidates and parties in the last decade, predictability in everyday life and the rule of law have suffered. This book is about Russia's attempt to achieve democratization backwards, by holding elections without having created a modern state. This dilemma is the challenge that Russia presents to Vladimir Putin.
Keywords: Elections,Cuộc bầu cử,Political parties,Representative government and representation,Đảng chính trị,Đại diện chính phủ và đại diện; Russia (Federation),Liên bang Nga,Russia (Federation),Russia (Federation),Liên bang Nga,Liên bang Nga